Chemoinhibition of Mineralization of Urinary Stone Forming Minerals by Magnesium and Zinc Ions in Aqueous and Urinary Milieu - Rao, T.V.R.K.; Choudhary, V.K. (Asian Journal of Chemistry, 2010)
Chemoinhibition of mineralization of urinary stone forming minerals viz., calcium oxalate and calcium phosphate by magnesium and zinc ions, under different concentrations, have been studied in aqueous as well as urinary milieu. Inhibition efficiency has been studied in an experimental model. Crystals were isolated from the centrifugates of inhibited solutions in aqueous medium and their infrared spectra were studied. Results revealed that magnesium ions at different concentrations show uniformly good inhibition of mineralization of calcium phosphate by 22.59-30.63 % above blank in aqueous and 18.01-29.67 % above blank in urinary media. Zinc ions, however, showed a good inhibition of calcium oxalate mineralization in the range of 6.50-17.07 % above blank in aqueous and 0-35.32 % above blank in urinary media. Infrared spectra of the crystals, isolated from the centrifugates of inhibited solutions, evidenced a bridging mode of C=O of oxalate and a coordinated mode of phosphate. This suggests soluble complexation to be the probable mechanism behind inhibition of oxalate and phosphate mineralization by magnesium and zinc ions.